Maternal supplementation of different trace mineral sources on broiler breeder production and progeny growth and gut health - de Arruda Roque, Fabricia; Chen, Juxing; Araujo, Raquel B; Murcio, André Luis; de Souza Leite, Brunna Garcia; Dias Tanaka, Mylena Tückmantel; Granghelli, Carlos Alexandre; Pelissari, Paulo Henrique; Bueno Carvalho, Rachel Santos; Torres, David; Vázquez‐Añón, Mercedes; Hancock, Deana; et al. (Frontiers in Physiology, 2022)
Trace mineral minerals Zn, Cu, and Mn play important roles in breeder production and progeny performance. The objective of this study was to determine maternal supplementation of trace mineral minerals on breeder production and progeny growth and development. A total of 540 broiler breeders, Cobb 500 (Slow feathering; 0–66 weeks old) were assigned to one of three treatment groups with the same basal diet and three different supplemental trace minerals: ITM–inorganic trace minerals in sulfates: 100, 16, and 100 ppm of Zn, Cu, and Mn respectively; MMHAC -mineral methionine hydroxy analog chelate: 50, 8, and 50 ppm of bis-chelated MINTREX®Zn, Cu and Mn (Novus International, Inc.), and TMAAC - trace minerals amino acid complex: 50, 8, and 50 ppm of Zn, Cu, and Mn. At 28 weeks of age, eggs from breeder treatments were hatched for progeny trial, 10 pens with 6 males and 6 female birds per pen were fed a common diet with ITM for 45 days. Breeder production, egg quality, progeny growth performance, mRNA expression of gut health associated genes in breeder and progeny chicks were measured. Data were analyzed by one-way ANOVA; means were separated by Fisher’s protected LSD test. A p-Value ≤ 0.05 was considered statistically different and 0.1 was considered numerical trend. Breeders on ITM treatment had higher (p < 0.05) body weight (BW), weight gain and lower (p < 0.05) feed conversion ratio (FCR) from 0 to 10 weeks, when compared to birds fed MMHAC. MMHAC significantly improved egg mass by 3 g (p < 0.05) and FCR by 34 points (0.05 < p < 0.1) throughout the reproductive period (26–66 weeks) in comparison to ITM. MMHAC improved (p < 0.01) egg yolk color versus (vs.) ITM and TMAAC in all periods, except 28 weeks, increased (p < 0.01) eggshell thickness and resistance vs. TMAAC at 58 weeks, and reduced (p < 0.05) jejunal NF-κB gene expression vs. TMAAC at 24 weeks. There was a significant reduction in tibial dry matter weight, Seedor index and resistance for the breeders that received MMHAC and/or TMAAC when compared to ITM at 18 weeks. Lower seedor index but numerically wider tibial circumference was seen in hens fed MMHAC at 24 weeks, and wider tibial circumference but lower tibial resistance in hens fed TMAAC at 66 weeks. Maternal supplementation of MMHAC in breeder hens increased (p < 0.0001) BW vs. ITM and TMAAC at hatching, reduced (p < 0.05) feed intake vs. ITM at d14 and d28, and improved (p < 0.01) FCR and performance index vs. TMAAC at d28, reduced (p < 0.01) NF-κB gene expression and increased (p < 0.05) A20 gene expression vs. TMAAC on d0 and vs. ITM on d14, reduced (p < 0.05) TLR2 gene expression vs. ITM on d0 and vs. TMAAC on d14, increased (p < 0.05) MUC2 gene expression vs. both ITM and TMAAC on d45 in progeny jejunum. Overall, these results suggest that supplementation with lower levels of MHA-chelated trace minerals improved breeder production and egg quality and reduced breeder jejunal inflammation while maintaining tibial development in comparison to those receiving higher inorganic mineral supplementation, and it also carried over the benefits to progeny with better growth performance, less jejunal inflammation and better innate immune response and gut barrier function in comparison to ITM and/or TMAAC.